Cytotoxicity effect of natural and synthetic girinimbines and their deritatives against human lung cancer cell lines A549 - Osman, Fatin Nurul Atiqah; Mohd Nor, Siti Mariam; Nafiah, Mohd Azlan (Faculty of Science and Technology, Universiti Kebangsaan Malaysia, 2021)
The present study was designed to evaluate the anticancer properties of girinimbine and its derivatives. Two different routes for the synthesis of girinimbine involving a two-step reaction or a one-pot reaction were studied. Girinimbine was synthesised through metal-catalysed heterocoupling, indole ring closure, ether formation, and Claisen cyclisation. Girinimbine derivatives were prepared by the semi-synthesis of isolated girinimbine from Murraya koenigii through alkylation or acylation reactions. Natural and synthetic girinimbines, five derivatives of N-substituted girinimbine, and three intermediates from the synthesis of girinimbine were evaluated for cytotoxicity activity against human lung cancer (A549) and normal lung (MRC-5) cell lines. The structures of all the synthesised compounds were confirmed by spectroscopic analysis and comparison with published data. The cytotoxicity assay showed that the natural girinimbine and nitrobiphenyl intermediate exhibited high toxicity (IC50 6.2 and 17.0 μg/mL, respectively), whereas other compounds displayed moderate toxicity activity (IC50 24.0 - 40.6 μg/mL) on A549 cells. All of the compounds demonstrated selectivity to A549 cancer cell lines with the SI values ranging from 2.70 to 4.68 (SI > 2), except for two N-alkylated girinimbines with the SI values of 0.93 and 1.70.